Thirteen Years of Continuous Compulsory Education to Achieve SDG 4 and Welcome Golden Indonesia 2045 - Hadiyanto Hadiyanto; Abdul Hakim; Sari Febrianti; Anggun Mawar Lestari (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The study aims to identify and synthesize the major factors contributing to Out-of-School Children (OSC) in Indonesia as evidence for supporting the implementation of the 13-year compulsory education policy mandated by Law of the Republic of Indonesia Number 59 of 2024 concerning the National Long-Term Development Plan (2025–2045), which supports the realization of Golden Indonesia 2045. Method: The study employed a literature review with a meta-analysis approach. A total of 66 relevant research articles conducted across 34 provinces in Indonesia were analyzed, representing 854 out-of-school respondents. Data in the reviewed studies were collected through interviews and questionnaire surveys. The identified factors were synthesized and ranked based on their frequency of occurrence across the studies. Results: The analysis identified 25 factors influencing children to drop out of school or not continue their education. The six dominant factors were parents' economic constraints (81.8%), children's low interest and motivation to attend school (74.2%), unfavorable peer environment and unemployment (68.2%), limited parental attention to education (62.1%), parents' educational background (34.8%), and long distance between home and school (33.3%). The remaining 19 factors each contributed less than 30%. These findings indicate that economic, family, individual, and environmental factors simultaneously influence school participation. Novelty: The study provides a comprehensive synthesis of evidence from studies covering all 34 provinces in Indonesia and offers a national-level prioritization of the determinants of out-of-school children. The findings serve as an evidence-based reference for designing targeted interventions and educational policies to support the successful implementation of the 13-year compulsory education program through both formal and non-formal education pathways.